Serum magnesium behavior in professional cyclists after a multi-stage competition - Codova, A.; Mielgo-Ayuso, J.; Bonilla, L. (European Journal of Sports & Exercise Science, 2015)
The aim of this study was to determine the effects of continuous, repetitive and intense exercise, such as the stage cycling race, on the serum Mg. Fourteen male cyclists from two professional cycling teams were recruited to participate in the investigation.The cyclists were tested at three specific points around the "Vuelta a Mallorca": a) before start the race T0, b) In the middle of the race T1 - before start 3rd stage and c) last race T2. Serum Ca and Mg, Creatine kinase (CK) and total proteins (TP) were measured.Red blood cell counts, hemoglobin (Hb), and hematocrit (Hct) were determined. Serum Mg levels have showed a decrease tendency during the race (T0: 22.93±0.96 vs. T2: 20.25±0.49 mg/L).However, serum Ca levels at the end of race was significant lower than at begin of these (T0: 107.79±3.43 vs. T2: 96.88±1.80 mg/L). In summary, long term exercise along a race from 5 days was accompanied by small decrease in serum Mg seemed to be related to the redistribution of Mg. Our main findings support the hypothesis that serum Mg levels decrease during daily strenuous endurance stages of cycling stages race.